(untitled) (Journal of Environmental Bioremediation and Toxicology, 2014)
Kinetic equations, which describe the activity of an enzyme or a microorganism on a particular substrate, are crucial in understanding many phenomena in biotechnological processes. They allow the mathematical prediction of growth parameters important for identifying key parameters for controlling growth. We remodeled the published work on chromate reduction by Bacillus sp. (JUBTCR3) using several more growth kinetic models such as Monod, Teissier, Andrews and Noack, Aiba, Webb (Edward), Yano and Koga, Han and Levenspiel and Luong and evaluated the accuracy of the fitted model using statistical analysis such as root mean square (rmse), adjusted coefficient of determination (R2), corrected Akaike Information Criterion (AICc), Bias Factor, Accuracy Factor and f-test. the calculated value for the Haldane constants in this work such as maximal growth rate, half saturation constant and half inhibition constant rate symbolized by umax, ks, and ki, were 0.07 hr-1, 17.4 mg/dm3 and 102.95 mg/dm3, respectively. The true umax where the gradient for the slope is zero for the Haldane model was approximately 0.037 h-1 at 42 mg/dm3 chromate. the results indicate that the exhaustive use of mathematical models on available published results could support published results using comparative analyses of more models backed by statistical analyses that can provide new knowledge on the way toxic substance inhibit growth rate in microbes.